Etnolinguistik: Penamaan Benda di Sekitar Rumah Pada Bahasa Jawa (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to explain the naming of objects around the house in Javanese through the application of ethnolinguistic studies. This research is included in the qualitative descriptive research category. The objects discussed in this research are objects around the house in Javanese through information and facts in the form of speech which means objects around the house. The data collected utilized the listening method, namely the skillful free-involved listening technique. The data description used in this research is an interactive model. The results of the research show that the mention of objects around the house in Java can be grouped based on their placement, so the grouping consists of objects around the house.